Fiscal Decentralization, Financial Decentralization and Macroeconomic Governance - Dexu, He; Wenlong, Miao (China economist (Beijing, China), 2022)
Improvement of the macroeconomic governance system as an important part of the national governance system is a key initiative to address major economic problems in the new era. The coordination and economic regulatory effects of fiscal and monetary policies are subject to the arrangements of fiscal and financial decentralization systems.Analysis revealed a mismatch between China's fiscal income decentralization and fiscal spending decentralization, as manifested in the clear decentralization of fiscal revenue and vague decentralization of fiscal spending; in pursuing local economic stability,local governments seek other sources of revenue and compete for financial resources, as manifested in apparent financial centralization and implicit financial decentralization,causing financial decentralization to be inconsistent between various levels of government and between government and the market. The above-mentioned problems are reflected in mutual conversion between public finance and financial intermediation as two financial allocation methods and mutual transmission between fiscal and financial risks, making the case for enhancing coordination between fiscal and monetary policies. In creating a scientific macroeconomic governance system, therefore, we must establish clear local government responsibilities, reduce the proportion of local fiscal spending, clarify the orientations and relief boundary of fiscal and monetary policies, moderately decentralize financial powers, and give better play to the role of local governments in improving the quality of economic development and controlling major risks.